Meloidogyne paranaensis and Meloidogyne exigua in coffee plantation from the South of Minas Gerais State - Salgado, Sonia Maria Lima; Guimarães, Natálya Monique R. B.; Botelho, César Elias; Tassone, Guilherme A. T.; Marcelo, Ana Luiza; Souza, Simone Ribeiro de; Oliveira, Rosângela D. Lima; Ferreira, Daniel Furtado (Coffee Science - ISSN 1984-3909, 2015)
The cities in the South of Minas Gerais, which is the main coffee producer region in Brazil, would face a serious risk of productivity loss if more aggressive root-knot nematodes species, such as Meloidogyne paranaensis. In order to prevent the dissemination of this nematode, it is necessary to know the occurrence outbreaks and distribution of Meloidogyne spp. in this region. Then, objective was to investigate Coffea arabica plantations of some coffee-producing cities in the South of Minas Gerais by root sampling, diagnosis and mapping of outbreaks. The total of 162 samples was calculated according to the planting area and coffee production in the production areas in some cities. The root-knot nematodes were found in 32.7% of them. The species M. exigua in 90.5%, and M. paranaensis in 9.5% of the detections. The occurrence of M. exigua and M. paranaensis was observed in the cities sampled, except Guaranésia, where no root-knot nematode was present. Esterase phenotypes E1 and E2 were found in M. exigua populations, highlighting the E2 phenotype in most cities (Guaxupé, Monte Belo, Monte Santo de Minas, Muzambinho and São Pedro da União). M. paranaensis (P1 phenotype) was detected in Coqueiral and Alpinópolis causing plant mortality. This suggest that is necessary the use of phytossanitary approaches.